A Close-up Look at Screens for Excluding Asian Citrus Psyllids - Timothy A. Ebert; Arnold W Schumann; Laura Waldo; Daniel Stanton; Philippe Rolshausen (EDIS, 2021)
Building a physical barrier around citrus trees or groves can prevent contact between trees and Asian citrus psyllids, the carrier of the pathogen that causes huanglongbing. This new 4-page article is for growers, scientists, and industries that are interested in this approach to protect citrus from huanglongbing. Written by Timothy A. Ebert, Arnold W. Schumann, Laura Waldo, Daniel Stanton, and Philippe Rolshausen, and published by the UF/IFAS Department of Soil and Water Sciences.